Studi Fenomenologis Kepatuhan Terhadap Standar Akuntansi Pemerintahan Dalam Pelaporan Aset Biologis (Studi Kasus: Organisasi “X”) - Zulkarnain, Arlin; Fanani, Zaenal (AKTSAR: Jurnal Akuntansi Syariah, 2018)
Implementation of SAP related biological assets generate a polemic against the compliance Financial Statements preparation of public sector organizations in Indonesia. The objectives of this study were to: (i) investigate the phenomenon of understanding/interpretation of public sector management SAP in the preparation of financial statements related to the treatment of biological assets; (ii) reveal the meaning of phenomena gained during the study; (iii) provide inputs based on summarized meanings, in an effort to improve SAP, government accounting policies, or related rules. This research used qualitative approach with the type of phenomenology study. Selected research sites in "X" organizations that have large quantities of biological assets with a focus on research sites at two production centers and vertical agencies (Directorate General and Secretariat General c.q. Financial Bureau). The results show that management applies as if obedient according to their understanding and interpretation of SAP. Management makes decisions regarding accounting policies with the justification of a problem that does not yet have a guideline. One example of measuring the inventory value of biological assets derived from its own production is by using the non-tax rate. In addition, the use of fair value today and in the future, is still an obstacle in the implementation of government organizations.